Effect of heat and microwave treatments on phenolic compounds and fatty acids of turmeric (Curcuma longa L.) and saffron (Crocus sativus L.) - Cortez, Mariela Valentina (2020)
Turmeric and saffron are spices with fatty acids and phenolic compounds that exert several human health benefits. Nonetheless, their bioavailability may be reduced by cooking that involves high temperatures. Thus, our aim was to evaluate the effects of domestic heat treatments with respect to untreated controls on these molecules assessed by spectrophotometry and gas chromatography: microwaving, boiling under pressure and boiling without it (compared by ANOVA, p < 0.05). All treatments reduced phenolic compounds in saffron, whereas only microwaving decreased them in turmeric. Turmeric curcumin was reduced by microwaving and boiling under pressure. Turmeric and saffron showed a different fatty acid profile, which was differentially affected depending on the treatment. In conclusion, although the functional and nutritional quality of these spices can be affected, turmeric is more resistant to heat than saffron and shows a better lipid profile with high unsaturated fatty acids even after treated. Also, boiling preserved potential health-promoting phenolic compounds and some unsaturated fatty acids. Although a risk of bioactive compound loss exists, the correct cooking method can reduced it.